A rhetorical analysis on Rodrigo Duterte's humor & threat rhetoric on his "war on drugs" speeches - Rubiato, Jan Augustus M. (2018)
A Rhetorical Analysis of Rodrigo Duterte?s Humor & Threat Rhetoric on His ?War on Drugs? Speeches is an analysis discussing the use by President Rodrigo Duterte of the Humor and Threat rhetoric style in his speeches about the ?War on Drugs? campaign. The study only focused on five humor speeches and another five of the threat speeches. The selected speeches were made during the first six to eight-month time frame after Duterte assumed office as the 16th President of the Philippines, the main guide on how the study was conducted was Kenneth Burke?s Dramatism Theory and the Dramatism Pentad which consists of the act, scene, agent, purpose, agency elements. By identifying the predominant ratios between the elements, it became clearer for the researcher how, when, and why Duterte employs the Humor and Threat rhetoric. It was found out in the study that Duterte employs these rhetoric styles for four reasons: First, it when he answers both local and international criticisms against the anti-illegal drugs campaign of his administration. Second, is when he warns all law violators to stop doing illegal activities in the country. Third, is when he explains how drugs can destroy a person, his family, and the country. Finally, is when he wants to show his sense of nationalism, patriotism and uncompromising love for his country and his people. It was also evident in the results of the study that Duterte uses the Threat rhetoric more than humor. This finding was proved by two concepts at the end of the study. his devil terms were thrice the number of the God terms he used in the speeches subject of this study. The next proof was in the instances when he tries to inject humor by the use of curses, expletives and threats. In the speeches covered by this study, President Duterte showed his peculiar way of driving home his point and unique manner of getting his message across; that he employs the threat of use of force or violence for the good and welfare of his country and people.